2015
DOI: 10.1002/cbic.201500213
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐Based Protein Profiling of Rhomboid Proteases in Liposomes

Abstract: Although activity-based protein profiling (ABPP) has been used to study a variety of enzyme classes, its application to intramembrane proteases is still in its infancy. Intramembrane proteolysis is an important biochemical mechanism for activating proteins residing within the membrane in a dormant state. Rhomboid proteases (intramembrane serine proteases) are embedded in the lipid bilayers of membranes and occur in all phylogenetic domains. The study of purified rhomboid proteases has mainly been performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…For rhomboids, several activity-based probes have been reported [35,37,45]. They enable a variety of different detection methods including gel-based analysis [35,37,45], fluorescent polarization in 96-well plate format [35], and fluorescent microscopy [46]. The structures and applications of rhomboid ABPs will be discussed in more detail in Section 4.…”
Section: Activity-based Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…For rhomboids, several activity-based probes have been reported [35,37,45]. They enable a variety of different detection methods including gel-based analysis [35,37,45], fluorescent polarization in 96-well plate format [35], and fluorescent microscopy [46]. The structures and applications of rhomboid ABPs will be discussed in more detail in Section 4.…”
Section: Activity-based Probesmentioning
confidence: 99%
“…However, this study showed that the identification of inhibitors is not affected by the environment, confirming that micelle-solubilized rhomboids are a suitable model system. Furthermore, it was shown that fluorescent ABPs can be used to visualize rhomboids in giant unilamellar vesicles by fluorescence microscopy [46].…”
Section: Activity-based Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of the compounds for a variety of rhomboids and off-target effects against human serine hydrolases were tested using activity-based probe approaches. 36,37 This effort provided submicromolar, partially reversible, and selective rhomboid protease inhibitors based on a novel and modifiable scaffold.…”
mentioning
confidence: 99%
“…Mass spectrometry and mutagenesis were used to establish the reaction mechanism of rhomboid inhibition by saccharins, and the in vivo potency was determined in Escherichia coli . The selectivity of the compounds for a variety of rhomboids and off-target effects against human serine hydrolases were tested using activity-based probe approaches. , This effort provided submicromolar, partially reversible, and selective rhomboid protease inhibitors based on a novel and modifiable scaffold.…”
mentioning
confidence: 99%